Lactobacillus rhamnosus GG supernatant enhance neonatal resistance to systemic Escherichia coli K1 infection by accelerating development of intestinal defense - He, Xiaolong; Zeng, Qing; Puthiyakunnon, Santhosh; Zeng, Zhijie; Yang, Weijun; Qiu, Jiawen; Du, Lei; Boddu, Swapna; Wu, Tongwei; Cai, Danxian; Huang, Sheng-He; Cao, Hong (Scientific reports, 2017)
The objective of this study was to determine whether Lactobacillus rhamnosus GG culture supernatant (LCS) has a preventive effect against gut-derived systemic neonatal Escherichia coli (E. coli ) K1 infection. The preventive effects were evaluated in human colonic carcinoma cell line Caco-2 and neonatal rat models. Our in vitro results showed that LCS could block adhesion, invasion and translocation of E. coli K1 to Caco-2 monolayer via up-regulating mucin production and maintaining intestinal integrity. In vivo experiments revealed that pre-treatment with LCS significantly decrease susceptibility of neonatal rats to oral E. coli K1 infection as reflected by reduced bacterial intestinal colonization, translocation, dissemination and systemic infections. Further, we found that LCS treated neonatal rats have higher intestinal expressions of Ki67, MUC2, ZO-1, IgA, mucin and lower barrier permeability than those in untreated rats. These results indicated that LCS could enhance neonatal resistance to systemic E. coli K1 infection via promoting maturation of neonatal intestinal defense. In conclusions, our findings suggested that LCS has a prophylactic effect against systemic E. coli K1 infection in neonates. Future studies aimed at identifying the specific active ingredients in LCS will be helpful in developing effective pharmacological strategies for preventing neonatal E. coli K1 infection.